The Apemen Faces Database (ApeFD) - Zdzisław Lewandowski; Slawomir Wacewicz; Juan Olvido Perea-García; Vojtěch Fiala; Marta Sibierska; Anna Szala; Dariusz P. Danel (Scientific Data)
Abstract The Apemen Faces Database is a novel and versatile stimulus set designed for research in behavioral biology, evolutionary psychology, and related fields. The dataset comprises 620 photorealistic, artificially generated facial images of 31 generalized hominin models, available in multiple ocular coloration variants (31 hominins x 20 color variants). Each of the 31 facial portraits is paired with geometric morphometric data and norming information that includes perceptual ratings of six constructs (Threat, Sociability, Trustworthiness, Health, Age, and Masculinity). Further, editable .psd files enable easy generation of a wide spectrum of great ape eye phenotypes. The images were designed to be morphologically diverse, sufficiently humanlike to elicit social attributions, yet clearly non-human. This unique “humanlike but not human” design facilitates the study of face perception beyond the boundaries of extant human variation, offering novel opportunities for investigating cognitive and perceptual mechanisms in both humans and non-human primates.